Anne of Avonlea - Montgomery, L. M. (Lucy Maud), 1874-1942 (New York : Laurel Leaf Books, 1992)
In this sequel to Anne of Green Gables, sixteen-year-old Anne Shirley becomes a schoolteacher in a small village on Prince Edward Island.
Includes necklace with charm.
Keywords: Orphans -- Fiction; Teachers -- Fiction; Islands -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction